Cognitive impairments and depression in Parkinson's disease: a follow up study. - Starkstein, S E (1990)
The presence of depression and cognitive impairments was examined in seventy patients with Parkinson's disease (PD). Forty nine patients of this original cohort were re-examined between three and four years after the first evaluation. While both depressed and non-depressed patients showed a significant decline in cognitive function during the follow up period, intellectual decline was significantly more severe for the depressed group. Depressed patients also showed a faster rate of progression of motor signs (mainly tremor) than the non-depressed group. Patients that died during the follow up period showed significantly more cognitive impairments than patients who were alive at follow up. These findings suggest that either there may be two forms of PD: one with depression and rapid cognitive decline and one without depression and a gradual cognitive decline; or that the mechanisms of cognitive impairment in PD and depression may interact to produce a more rapid evolution in cognitive impairment among PD patients with a previous depression than among patients without a previous depression.